Respostas

2014-04-19T10:47:48-03:00
G) ^=(-3)²-4*1*(-4)
     ^=9+16
    ^=25
X=3+-RAIZde 25 / 2*1
x¹= 8 / 2 = 4
x²= -2 / 2 = -1
1 5 1
A melhor resposta!
2014-04-19T10:57:02-03:00
G) x²-3x-4=0
Δ = b² - 4ac
Δ = (-3)² - 4(1)(-4)
Δ = 9 + 16
Δ = 25
x = -b +- √Δ /2a
x = 3 +- 5 /2
x1 = 8/2 = 4

x2 = -2/2 = -1

h) 5x²+4x-1=0
Δ = (4)² - 4(5)(-1)
Δ = 16 + 20
Δ = 36
x = -4 +- 6 /10
x1 = 2/10 = 1/5
x2 = -10/10 = -1

k)9x²-6x+1=0
Δ = (-6)² - 4(9)(1)
Δ = 36 - 36
Δ = 0
x = 6 +- 0 /18
x1 = x2 = 6/18 = 1/3

q)x²-12x+36=0
Δ = (-12)² - 4(1)(36)
Δ = 144 - 144
Δ = 0
x = 12 +- 0 /2
x1 = x2 = 12/2 = 6

v) 2x²=5x-8
2x²-5x+8=0
Δ = (-5)² - 4(2)(8)
Δ = 25 -  64
Δ = -39
x = 5 +- i√39 /4
x1 = 5/4 + i√39/4 = 1/4 (5 + i√39)
x2 = 5/4 - i√39/4 = 1/4 (5 - i√39)

w) x²-x=x-1
x²-x-x+1=0
x²-2x+1=0
Δ = (-2)² - 4(1)(1)
Δ = 4 -  4
Δ = 0
x = 2 +- 0 /2
x1 = x2 = 2/2 = 1

z) 7x²+3x+1 =3x²
7x²-3x²+3x+1=0
4x²+3x+1=0
Δ = (3)² - 4(4)(1)
Δ = 9 - 16
Δ = -7
x = -3 +- i√7 /8
x1 = -3/8 + i√7/8 = 1/8 (-3 + i√7)
x2 = -3/8 - i√7/8 =  1/8 (-3 - i√7)
1 5 1